A fluorescent reporter for mapping cellular protein‐protein interactions in time and space. Issue 1 (19th March 2013) - Moreno, Daniel; Neller, Joachim; Kestler, Hans A; Kraus, Johann; Dünkler, Alexander; Johnsson, Nils
Abstract : We introduce a fluorescent reporter for monitoring protein–protein interactions in living cells. The method is based on the Split‐Ubiquitin method and uses the ratio of two auto‐fluorescent reporter proteins as signal for interaction (SPLIFF). The mating of two haploid yeast cells initiates the analysis and the interactions are followed online by two‐channel time‐lapse microscopy of the diploid cells during their first cell cycle. Using this approach we could with high spatio‐temporal resolution visualize the differences between the interactions of the microtubule binding protein Stu2p with two of its binding partners, monitor the transient association of a Ran‐GTPase with its receptors at the nuclear pore, and distinguish between protein interactions at the polar cortical domain at different phases of polar growth. These examples further demonstrate that protein–protein interactions identified from large‐scale screens can be effectively followed up by high‐resolution single‐cell analysis. Abstract : A method based on a combination of the Split‐Ubiquitin system with two spectrally different fluorescent proteins (SPLIFF) is shown to enable measurement of protein interactions in vivo with high spatial and temporal resolution in yeast. Synopsis: A method based on a combination of the Split‐Ubiquitin system with two spectrally different fluorescent proteins (SPLIFF) is shown to enable measurement of protein interactions in vivo with high spatial and temporal resolution in yeast. SPLIFF visualizes protein interactions with high spatial and temporal resolution. Spc72p and Kar9p interact with the MAP Stu2p at opposite poles of microtubules. Histone chaperone Nap1p and Kcc4 kinase interact preferentially at the bud site. F‐BAR protein Hof1p associates with the polarisome during cell fusion and cytokinesis.